Three types of ceramic coating applicability in automotive industry for wear resistance purpose - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2005)
Purpose - The aim of the research is to investigate the influence of ceramic coating on the wear performance of machine parts. Design/methodology/approach - Ductile cast iron parts were coated using ceramics. Three ceramics were used for this purpose. These coated parts were subjected to wear tests under a stable load. A pin-on-disc wear test apparatus was used. Findings - As a result of this study, the following findings are reported: According to ASTM G 99-90 pin-on-disc experiments, Cr2O3 was found to be best coating material with low wearing rate. Within row, Al2O3 and ZrO2 can be given. According to the previous work, motor parts for example piston ring, cylinder liner and engine valve can be coated with ceramic. In this study, it is observed that the figure of merit is increased in this study. Only wearing data is given in this research. The other results are also supporter of the results taken from the wearing experiments. As a result, due to the decrease in heat loss and coaling stability of part can provide good results. With these, by coating there is a decrease in oil reduction. Research limitations/implications - Coatings were limited with three ceramics, a stable load was used, and coated parts were subjected to wear test. Practical implications - For future work, instead of using other coating materials, Cr2O3 is used for the best coating material with low wearing rate. By this process, working life of the machine parts can be extended and a number of economical advantages may also be obtained. Originality/value - This paper fulfills identified information needs and offers practical help to the industrial firms working with ceramic coating and also to the academicians working on wear of materials.
Keywords: ceramics; coating processes; wear resistance; TRIBOLOGICAL PROPERTIES; MECHANICAL-PROPERTIES; SLIDING WEAR; GRAIN-SIZE; ZIRCONIA; FRICTION; BEHAVIOR; STRENGTH